CEFR implementation at the post-secondary level: teachers’ receptivity - Saiful Islam, Ahmad Sukri; Zubairi, Ainol Madziah; Saad, Mohammad Azannee; Preece, Abdul Shakour Duncan (The Asia Pacific Journal of Curriculum & Teaching (JuKu), Faculty of Education, Universiti Malaya, 2025)
The influence of the Common European Framework of Reference for Languages (CEFR) in teaching, learning and assessment has grown increasingly since 2001. Convinced of the potential benefits that the CEFR can bring to English language education in local contexts, Malaysia has enforced the CEFR in all levels of education from preschool to university, mainly to improve students' English proficiency and align local educational practices with international standards. Although the CEFR was officially introduced in 2017, starting with Standard 1 primary and Form 1 secondary school students, its implementation at the post-secondary level started late in 2020 and, since then, has remained largely unexplored. Against this background, the present study, based on a social constructivist case study methodology, conducted an in-depth interview with four post-secondary English teachers to explore their receptivity to the CEFR. The findings of the thematic analysis revealed four major dimensions, namely teachers’ knowledge, perceptions and practices, and the challenges of implementing the CEFR. The study ends with pedagogical and policy implications resonating with other similar contexts.